A Contemporary Connection to Historic Buildings Through Transparency and Reusability. Issue 3 (1st September 2015) - Nevzat, Meltem Zehra; Atakara, Cemil
Abstract : From the 19th century onwards, glass has been used intensively in buildings. During the design process, the importance of aesthetics is very common for architects in general. The application of glass walls as part of the building's structure has given flexibility in design together with transparency as well as aesthetics. Structural glass systems have been used in different building types for example office, residential, educational, commercial, transportation, cultural … Beyond the high - rise and high - tech buildings, structural glass systems have been applied also to historic buildings during their conservation process. The adaption of the structural glass system and the opportunity to reuse the existing building are other important aspects to be discussed. In this article, the literature review will be formed with a brief explanation of transparency in contemporary architecture, structural glass systems focusing on 'suspended glass systems with pre-stressed cable trusses' (SGSPCT) which has three application methods; 1) between floor systems 2) independent body systems 3) distance bridging systems and the reusability of existing buildings. The 'between floor system' which is commonly used as a contemporary solution technique for historic buildings together with its effects, will also be analysed with the help of a case study, Esma Sultan Mansion. This historic building's present glass structure will be studied to create an alternative proposal less dependent to the existing building. Another case study will be the Ballapais Abbey. Part of this gothic building (the common room) that has collapsed in the past will be analysed. An independent glass structured annex designed with SGSPCT will be proposed giving joint details of the adaptation to the existing building. This case of study is a literature analysis based on books, internet resources, articles and architectural drawings, like plans, sections and details related to the buildings. Both case studies will be proposing an alternative glass structured annex that is focusing on gained transparency and reusability in respect to the existing historic building.